2020
DOI: 10.23917/jurisprudence.v10i1.10974
|View full text |Cite
|
Sign up to set email alerts
|

Kebijakan Perlindungan Anak Terhadap Eksploitasi Seksual Melalui Nikah Siri Dalam Perspektif Hukum Nasional Di Indonesia

Abstract: Artikel ini bertujuan untuk mengkaji dan menganilisis kebijakan perlindungan bagi anak (perempuan) korban eksploitasi seksual melalui nikah siri yang marak terjadi di Indonesia. Metodologi: Penelitian ini menggunakan penelitian hukum doktrinal. Sumber informasi hukum menggunakan bahan hukum primer (peraturan dan dokumen relevan) untuk selanjutnya dilakukan analisis secara kualitatif. Pendekatan yang digunakan adalah perundangundangan, konseptual dan analisis dalam membantu pemecahan rumusan masalah. Temuan: Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The study of elementary school students in Surakarta, Indonesia showed that most students (98%) had low self-protection skills from sexual abuse [2]. The lower the social status, especially the social status of the child's family, the higher the potential for the child to be manipulated, made into a sexual object, because socially he is in a powerless condition [3]. Perpetrators of abuse are the closest people to the victim, such as the victim's stepfather, biological father, close family, neighbors, and friends.…”
Section: Introductionmentioning
confidence: 99%
“…The study of elementary school students in Surakarta, Indonesia showed that most students (98%) had low self-protection skills from sexual abuse [2]. The lower the social status, especially the social status of the child's family, the higher the potential for the child to be manipulated, made into a sexual object, because socially he is in a powerless condition [3]. Perpetrators of abuse are the closest people to the victim, such as the victim's stepfather, biological father, close family, neighbors, and friends.…”
Section: Introductionmentioning
confidence: 99%